Analysis of two-option integration of unmanned aerial vehicle and terrestrial laser scanning data for historical architecture inventory - Sobura, Szymon; Bacharz, Kamil; Granek, Grzegorz (Geodesy and Cartography, 2023)
The 3D reconstruction of historical and cultural heritage monuments is a procedure recommended by the UNESCO World Heritage Institution since 1985. It is crucial when conserving monuments and creating digital twins. Current 3D reconstruction techniques using digital images and terrestrial laser scanning (TLS) data are considered as cost-effective and efficient methods for the production of high-quality digital 3D models. In the presented study, laser scanning and close-range photogrammetry techniques and images taken by a low-cost unmanned aerial vehicle (UAV) were applied to quickly and completely acquire the point cloud and texture of a historic church in Poland. The aim of this study was to evaluate two options for integrating TLS and UAV data, using ground control points (GCP) measured by two independent techniques: tachymetry and laser scanning. The study shows that the 3D model created based on ground control points acquired by the laser scanning technique has a mean square error RMSEXYZ = 2.5 cm on the check points. The result obtained is not much larger than the second variant of data integration, for which RMSEXYZ = 1.7 cm. Thus, the TLS method was positively evaluated as a GCP measurement technique for the integration of UAV and TLS data and the creation of cartometric 3D models of religious buildings.